Optimal Control of the Alkylation Process Reactors - Aygun Safarova; Elchin Melikov; Tamella Magerramova (Operational Research in Engineering Sciences: Theory and Applications, 2023)
Recent studies show that one of the most important issues of static optimization of structurally complex non-stationary technological processes is the development of appropriate methods for problem decomposition. The issue of optimization of non-stationary alkylation processes and ways to solve the problems arising in this regard has been investigated in this paper. It is known that there are several ways to increase economic efficiency of control systems for petrochemical technological processes.  It includes checking of instruments and regulators, identify improvements in the control and monitor of performance, etc. One of the main ways to increase the efficiency of control systems for technological processes which depend on current conditions is to develop models and algorithms that allowing control these processes in more optimal modes compared to current ones. In this regard, the presented article is relevant as it is dedicated to the development of optimal control algorithms for multistage petrochemical technological processes consisting of series-connected non-stationary technological devices.